The effect of solid solution temperature on the precipitation phase and properties of plasma arc welded joints of Inconel625 high temperature alloy. (1st December 2022) - Zhang, Zhongke; Chu, Shusheng; Xiong, Jianqiang; Jiang, Changming; Li, Xuanbai
Abstract: The effect of solid solution temperature on microstructure and mechanical properties of plasma welded nickel-based high temperature alloy Incone l625 was investigated by solid solution treatment (The solid solution temperature range is 950 °C to 1150 °C and the intergroup interval is 50 °C). The results show that after solid solution treatment at 950 °C, chain carbides are precipitated at the austenite grain boundary of the base material. With solid solution temperature increasing, carbon chains dissolve gradually at the grain boundary. When solution temperature is higher than 1050 °C, carbides at the grain boundary completely melt back into the matrix. At the weld, dendritic crystal and Laves phase dissolve with the increase of solid solution temperature. When the solid solution temperature is 1100 °C, the dendritic crystal and Laves phase at the weld completely melt into the matrix and transform into cellular crystals. When the solid solution temperature is increased to 1150 °C, the cellular crystal grows further at the weld. When the solid solution temperature is 1100 °C, the comprehensive mechanical properties of the joint are the best.